Advantages, effectiveness and efficiency of using neodymium nanoparticles by 3d finite element method (FEM) as an optothermal human cancer cells, tissues and tumors treatment under synchrotron radiation - Heidari, Alireza; Schmitt, Katrina; Henderson, Maria; Besana, Elizabeth (International Journal of Advanced Chemistry, 2019)
In the current study, thermoplasmonic characteristics of Neodymium nanoparticles with spherical, coreâ€“shell and rod shapes are investigated. In order to investigate these characteristics, interaction of synchrotron radiation emission as a function of the beam energy and Neodymium nanoparticles were simulated using 3D finite element method. Firstly, absorption and extinction cross sections were calculated. Then, increases in temperature due to synchrotron radiation emission as a function of the beam energy absorption were calculated in Neodymium nanoparticles by solving heat equation. The obtained results show that Neodymium nanorods are more appropriate option for using in optothermal human cancer cells, tissues and tumors treatment method. Â Â Â Scanning Electron Microscope (SEM) image of Neodymium nanoparticles with 50000x zoom. Â Â